2022
DOI: 10.1371/journal.pone.0267705
|View full text |Cite
|
Sign up to set email alerts
|

Biological sample donation and informed consent for neurobiobanking: Evidence from a community survey in Ghana and Nigeria

Abstract: Introduction Genomic research and neurobiobanking are expanding globally. Empirical evidence on the level of awareness and willingness to donate/share biological samples towards the expansion of neurobiobanking in sub-Saharan Africa is lacking. Aims To ascertain the awareness, perspectives and predictors regarding biological sample donation, sharing and informed consent preferences among community members in Ghana and Nigeria. Methods A questionnaire cross-sectional survey was conducted among randomly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…While some studies did not find a relationship between religious beliefs and donors’ willingness to donate (Merdad et al, 2017 ; Pawlikowski et al, 2022 ; Pulley et al, 2008 ; Singh et al, 2022 ), this study has identified that religion can play a crucial—albeit indirect—role in shaping future HCPs’ attitudes toward biobanking. Thus, it supports observation made by Machin et al’ ( 2020 ) who stresses the complexity of donation system and situate various body parts and body products within the hierarchy of systems involved in the donation process (tissues and cells, organs, biological systems, the person, family, community, culture, society, and nation) and stress that faith and culture are among the most important dimensions that influence people’s decision to donate.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…While some studies did not find a relationship between religious beliefs and donors’ willingness to donate (Merdad et al, 2017 ; Pawlikowski et al, 2022 ; Pulley et al, 2008 ; Singh et al, 2022 ), this study has identified that religion can play a crucial—albeit indirect—role in shaping future HCPs’ attitudes toward biobanking. Thus, it supports observation made by Machin et al’ ( 2020 ) who stresses the complexity of donation system and situate various body parts and body products within the hierarchy of systems involved in the donation process (tissues and cells, organs, biological systems, the person, family, community, culture, society, and nation) and stress that faith and culture are among the most important dimensions that influence people’s decision to donate.…”
Section: Discussioncontrasting
confidence: 64%
“…Simultaneously, as research biobanks in Poland were established only recently biobanking still rises many ethical, moral, or religious concerns to which religious people can object. Consequently, since religious people are more prone to frame biomedical research as controversial, religion can influence people’s motivations for nonparticipation in biobank research (Broekstra et al, 2021 ; Goodson & Vernon, 2004 ; Heredia et al, 2017 ; Lewis et al, 2013 ; Lipworth et al, 2009 ; McDonald et al, 2012 ; Sanderson et al, 2017 ; Singh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free and informed consent, as the process of engaging potential participants, remains the solution to avoid coercion and inducement. Similarly, majority in our previous study opined that donation for genomic research should be a personal decision[21]. Due to the nature of genomic and neurobiobanking research, participation would be determined by how well participants are recruited and retained in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Before the pandemic, brain banks existed in a small number of low-middle-income countries, and this limited infrastructure has been unstable given reasons that include lack of funding, population-specific sociocultural and linguistic barriers, and limited awareness about brain sample donation for research. 88,89 Nevertheless, as SARS-CoV-2 infections relentlessly continue, brain autopsies remain critical to validate experimental models, move beyond hypotheses and provide answers to the public about the natural evolution of COVID-19 and how vaccination and various treatments might minimize the effects of the virus on the human body.…”
Section: Unrepresentative Research and Call For Investing In Brain Au...mentioning
confidence: 99%